HUBUNGAN DAYA TARIK DAN POLA MENONTON PADA PROGRAM X-FACTOR RCTI TERHADAP KEPUASAN MENONTON - Jaka Atmaja (Jurnal Komunikasi, 2017)
One reality show program that attracts attention is the reality show X-Factor Indonesia. Impressions has a value of information and entertainment and educative get enough servings presented by television stations in Indonesia. Of phenomena that arise from the television, there is a change to the Patterns Watching the audience watching the show program .. business broadcasting station is required to have the widest possible creativity to produce a variety of interesting programs. This study aims to measure and describe how big the "Fascination and Patterns Watching Watching Student Satisfaction and Communication Academy student BSI Against Youth Force 2014 Program show" X-Factor Indonesia RCTI (period of May - July 31, 2015) ". This study uses a quantitative research with descriptive purposes and the survey as a tool method of collecting data through questionnaires, with a sample of 60 respondents disharing through slovin formula. an idea that the appeal of the show X-Factor program against the respondents have a high appeal and provide the satisfaction of watching the respondents to the program X-Factor Indonesia. From these results, showed that between Fascination (X1) with the Spectator Satisfaction (Y) significant values 0.00 <0.05, which means there is a significant correlation and has a very strong relationship that is equal to 0, 976. Furthermore, between Pola Watching (X2) with the Spectator Satisfaction (Y) significant values 0.00 <0.05, which means there is a significant correlation and has a very strong relationship that is equal to 0.985. Furthermore, between Fascination (X1) with Pattern Watch (X2) significant values 0.00 <0.05, which means there is a significant correlation and has a very strong relationship that is equal to 0, 972. Thus the appeal and Patterns Watching and mutual satisfaction audience associated positive and strong.Key words: Reality Show Program, X-Factor Indonesia, At RCTI